2024
DOI: 10.1038/s41419-024-06722-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mitochondrial protein YME1L to inhibit osteosarcoma cell growth in vitro and in vivo

Xu Sun,
Ce Shi,
Jin Dai
et al.

Abstract: Exploring novel diagnostic and therapeutic biomarkers is extremely important for osteosarcoma. YME1 Like 1 ATPase (YME1L), locating in the mitochondrial inner membrane, is key in regulating mitochondrial plasticity and metabolic activity. Its expression and potential functions in osteosarcoma are studied in the present study. We show that YME1L mRNA and protein expression is significantly elevated in osteosarcoma tissues derived from different human patients. Moreover, its expression is upregulated in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…The role of the Akt/mTOR signaling pathway in osteosarcoma has been extensively investigated, revealing that the augmentation of this signaling cascade holds paramount significance in inhibiting autophagy and accelerating proliferation, invasion, metastasis, cell cycle progression, and the overall progression of osteosarcoma ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the Akt/mTOR signaling pathway in osteosarcoma has been extensively investigated, revealing that the augmentation of this signaling cascade holds paramount significance in inhibiting autophagy and accelerating proliferation, invasion, metastasis, cell cycle progression, and the overall progression of osteosarcoma ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al. found that the overexpression of YME1L stimulated osteosarcoma cell growth, likely by sustaining mitochondrial function and activating the Akt-mTOR pathway ( 40 ). Zhu et al.…”
Section: Discussionmentioning
confidence: 99%